PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PT.IKAPHARMINDO PUTRAMAS CABANG MEDAN - Ardiansyah Harahap (Universitas Medan Area, 2020)
Influence of HR Development and Organizational Commitment on Employee Performance at Medan branch of PT. Ikapharmindo Putramas, Skripsi, 2019.The purpose of this study was to find out and analyze the Effect of HR Development and Organizational Commitment on Employee Performance at PT. Ikapharmindo Putramas Medan Branch.The research method used is associative research, where the variable is measured by a Likert scale. The method of data collection is done by interview (interview), with a list of questions (questionnaire) and study documentation. The population in this study were all employees at the level of PT. Ikapharmindo Putramas Medan Branch, amounting to 65 people. Sampling with a saturated sampling method or better known as census. In this study the total population is relatively small, as many as 65 people. Data processing uses SPSS version 23 software, with descriptive analysis and hypothesis testing of multiple regression analysis.The results of the study show that: (1) partially the HR Development variable influences Employee Performance at the Medan Branch of PT. Ikapharmindo Putramas (2) partially the Organizational Commitment variable influences Employee Performance at Medan Branch of PT. Ikapharmindo Putramas ;; (3) simultaneously there is a positive and significant influence between the variables of HR Development and Organizational Commitment affecting Employee Performance at PT. Ikapharmindo Putramas Medan Branch.